2017
DOI: 10.1002/adv.21824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal resistance and mechanical properties of injected molded stereocomplex of poly(l‐lactic acid) and poly(d‐lactic acid) with various molecular weights

Abstract: Poly(l-lactic acid) (PLLA) and poly(d-lactic acid) (PDLA) with various molecular weights (MW) were melt blended in equivalent proportions, and then followed by injection molding to form polylactide stereocomplex (sc-PLA). The crystalline structures, thermal resistance, and mechanical properties of the formed sc-PLA were then investigated in detail. The results showed stereocomplex crystallites (sc) were formed predominantly in all the sc-PLA regardless of the MW of the PLLA or PDLA pellets, and a small amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Studies have confirmed that stereoselective association between D-and L-polymers occurred preferably when PDLA and PLLA were blended in equivalent proportions (1:1) Ikada 1993, 1999). However, homo-crystallites (hc) and stereocomplex crystallites (sc) were reported to coexist, although sc crystallites predominated, in sc-PLA manufactured by melt blending equivalent proportions of PLLA/PDLA, followed by conventional compression or injection molding (Li et al 2018;Srithep et al 2015). The obtained sc-PLA showed inferior mechanical properties to those of PLLA or PDLA, likely due to degree of polymerization (DP) loss caused by the high temperature during the melting process (Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that stereoselective association between D-and L-polymers occurred preferably when PDLA and PLLA were blended in equivalent proportions (1:1) Ikada 1993, 1999). However, homo-crystallites (hc) and stereocomplex crystallites (sc) were reported to coexist, although sc crystallites predominated, in sc-PLA manufactured by melt blending equivalent proportions of PLLA/PDLA, followed by conventional compression or injection molding (Li et al 2018;Srithep et al 2015). The obtained sc-PLA showed inferior mechanical properties to those of PLLA or PDLA, likely due to degree of polymerization (DP) loss caused by the high temperature during the melting process (Xu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic acid) (PLA) can replace traditional plastic in food packaging [ 1 , 2 , 3 , 4 , 5 , 6 ], bioengineering materials [ 7 , 8 , 9 ], composites [ 10 , 11 , 12 ] and other fields due to its good biodegradability, biocompatibility, and processability. However, PLA still has many inherent defects, such as the long degradation period and poor hydrophilicity, as well as low heat resistance which may increase PLA processing difficulty [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, this review focuses on discussing recent progress in the development of methodologies for preparing PLA-SC ( Figure 1 ), which not only includes scientific mechanisms for the origin of PLA-SC formation enhancement from each method but also highlights their processing-structure-property relationship for different applications including engineering plastics, biomedicine, and bioelectronics. We want to note, as a mini-review, there is no attempt to be comprehensive, and interested readers can find many excellent reviews on relevant topics of PLA-based materials including material synthesis, processing, macroscopic property, and applications that provide a more in-depth discussion (Pan et al, 2017 , 2018 ; Li et al, 2018 ). Our goal is rather to provide a succinct summary about progress to date on technology development for enhancing PLA-SC formation in order to compel new or interdisciplinary researchers to enter the fray and inspire more progress in the field.…”
Section: Introductionmentioning
confidence: 99%